Opioid Consumption Patterns After Lumbar Microdiscectomy or Decompression. Issue 22 (15th November 2019) - Lovecchio, Francis; Premkumar, Ajay; Stepan, Jeffrey G.; Mejia, Dianna; Stein, Daniel; Patel, Dil V.; Lafage, Virginie; Derman, Peter; Khechen, Benjamin; Iyer, Sravisht; Lebl, Darren; Qureshi, Sheeraz; et al.
Abstract : Study Design: Prospective observational study Objective: The aim of this study was to record daily opioid use and pain levels after 1-level lumbar decompression or microdiscectomy. Summary of Background Data: The standardization of opioid-prescribing practices through guidelines can decrease the risk of misuse and lower the number of pills available for diversion in this high-risk patient population. However, there is a paucity of quantitative data on the "minimum necessary amount" of opioid appropriate for post-discharge prescriptions. Methods: At two institutions between September 2017 and 2018, we prospectively enrolled 85 consecutive adult patients who underwent one-level lumbar decompression or microdiscectomy. Patients with a history of opioid dependence were excluded. Daily opioid consumption and pain scores were collected using an automated text-messaging-based platform for 6 weeks or until consumption ceased. Refills during the study period were monitored. Patients were asked for the number of pills left over and the method of disposal. Opioid use was converted to oral morphine equivalents (OMEs). Results are also reported in terms of "pills" (oxycodone 5 mg equivalents) to facilitate clinical applications. Risk factors were compared between patients in the top and bottom half of opioid consumption. Results: Total opioid consumption ranged from 0 to 118 pills, with a median consumption of 32 pills (236.3 OME). Seventy-five percent of patients consumed ⩽57 pills (431.3 OME). Mean Numeric Rating Scale pain scores declined steadily over the first 2 weeks. By postoperative day 7 half of the study population had ceased taking opioids altogether. Only 22.4% of patients finished their initial prescription, and only 9.4% of patients obtained a refill. Conclusion: These data may be used to formulate evidence-based opioid prescription guidelines, establish benchmarks, and identify patients at the higher end of the opioid use spectrum. Level of Evidence: 2 Abstract : A multicenter, prospective observational study of daily opioid use after one-level lumbar microdiscectomy or decompression found that half of patients consume ⩽32 tablets (oxycodone 5 mg equivalents), and that most patients cease opioid use within the first week.